CONSISTENT ASSESSMENT OF GRAIN QUALITY IN DURUM WINTER WHEAT BREEDING AND SEED-GROWING - M. M. Kopus; N. E. Samofalova; N. S. Kravchenko; N. P. Ilichkina; O. A. Dubinina; M. A. Leshchenko (Зерновое хозяйство России)
The article gives the results of a consistent assessment of breeding material of durum winter wheat with the use of express assessment methods as SDS-sedimentation and analysis of gliadin electrophoregrams. A consistent assessment allows forming a necessary amount of breeding samples with good and high grain quality right to competitive variety trials. It can be confirmed and characterized by the conventional and time-consuming technologies, that allows the farmer to choose promising competitive varieties with good quality and productivity when sending them to SVT. For the recent years of such practice we sent 11 varieties of durum winter wheat of FSBSI ARRIGC named after I.G. Kalinenko. They are ‘Aksinit’, ‘Kurant’, ‘Amazonka’, ‘Lazurit’, ‘Kristella’, ‘Oniks’, ‘Kiprida’, ‘Diona’, ‘Teya’, ‘Eyrena’ and “Yakhont’. They exceed the standard variety in grain quality, in productivity, in gliadins, that gives them opportunity to keep their position in the market of seeds.